Clonorchis sinensis-infected hepatocellular carcinoma exhibits distinct tumor microenvironment and molecular features - Chen, Junxian; Wei, Caibiao; Huang, Wencheng; Huang, Taijun; Zhou, Lingling; Xu, Yulong; Qin, Yuling; Lin, Qiumei; Liu, Fengfei; Pan, Xiaolan; Tang, Zeli; Yang, Weilong; et al. (Frontiers in Immunology, 2025)
ObjectivesClonorchis sinensis (Cs)-infected hepatocellular carcinoma (HCC) patients have a poorer prognosis than non-Cs-infected HCCs. However, the molecular mechanisms of Cs-infected HCC remain unclear. To address this, this study aims to uncover the tumor microenvironment and molecular features that may contribute to these poor outcomes.MethodsThe research involved bulk RNA sequencing of paired tumor and adjacent tissue samples from 10 Cs+ HCC and 10 Cs- HCC patients. Differentially expressed genes were identified, followed by enrichment analyses to reveal functional changes. Survival analysis of the top 10 up- and down-regulated genes in Cs+ HCC tumors was performed using TCGA database. Additionally, clinical data from 1,461 HCC patients were retrospectively analyzed to assess the impact of Cs infection on microvascular invasion and metastasis rates. In vitro assays were also conducted using Cs excretory/secretory products (CsESPs) to examine their effect on HCC cells and HUVECs.ResultsWe identified 785 up-regulated and 675 down-regulated genes in Cs+ HCC tumors compared to Cs- HCC tumors, enriched in pathways related to extracellular matrix remodeling and immunosuppression. Survival analysis revealed that the top 10 up-regulated genes are associated with HCC poor prognosis. Clinical data from 1,461 HCC patients showed Cs infection increased microvascular invasion and metastasis rates. In vitro, CsESPs products enhanced migration and invasion in HCC cells and promoted tube formation in human umbilical vein endothelial cells.ConclusionsThis study provides novel insights into the molecular landscape of Cs-infected HCC and underscores the Cs infection’s role in enhancing tumor migration, invasion and angiogenesis. The findings contribute to the understanding of parasitic infections in cancer progression and suggest potential prognostic markers for Cs+ HCC.